The Effect of Cognitive and Affective Aspects in Decision Making Using Balanced Scorecard - JESICA HANDOKO; GUDONO GUDONO (The Indonesian Journal of Accounting Research, 2013)
This study examines the effect of decision makers’ cognitive and affective aspects in decision making, especially when a firm implementing Balanced Scorecard (BSC). Cognitive aspect deals with decision makers’ cognitive capabilities and characteristics in utilizing all kinds of BSC measures, including common and unique measures. Affective aspect deals with negative emotions that often present in interpersonal relationships. There were three hypotheses being tested in a laboratory experiment using 2x2x2x2 mixed-subjects design. One hundred and sixty eight Accountancy and Management graduate students from Gadjah Mada University were randomly assigned in one of eight treatment cells.The results show that common and unique measures do have statistically significant effects on performance evaluation judgment and bonus allocation, and decision makers place greater emphasis on common than unique measures. These findings consistent with prior research that suggest sample with BSC knowledge will be able to utilizing both kinds of BSC measures. Although there were no statistically significant support for affect effect, this study provide important evidences for the BSC adopters to consider the makers’ cognitive (and affective) aspects if they want to pursue effective Balanced Scorecard.